Factor by grouping. 3x2 + 7x – 6 A. (3x – 2)(x – 3) B. (3x – 2)(x + 3) C. (x + 3)(3x + 2) D. (3x + 2)(x – 3)

Original conversation

User: Factor by grouping.
3x2
+ 7x – 6
A. (3x – 2)(x – 3)
B. (3x – 2)(x + 3)
C. (x + 3)(3x + 2)
D. (3x + 2)(x – 3)

Weegy: 3x2 - 7x - 6, the factored form is A. (3x + 2)(x - 3) andrewpallarca|Points 34842|

User: Factor the following trinomial.
w
18
– 9w
9
y
5
+ 14y
10

Weegy: Factor the following trinomial. w^18 9w^9y^5 14y^10
answer (w^9 - 2y^5)(w^9 - 7y^5). nexie10|Points 353|

User: . Simplify the expression. Write the answer using scientific notation.
8(8.8 x 1012)
A. 70.4 x 1012
B. 70.4 x 1024
C. 7.04 x 1013
D. 1.68 x 1013

Weegy: Simplify the expression. Write the answer using scientific notation. 8(8.8 x 1012) : A. 70.4 x 1012. blizzgalll|Points 70|

User: Order 34 x 102
, 1.2 x 107
, 8.11 x 10-3
, and 435 from least to greatest.

Weegy: 8.11 x 10^-3, 435, 34 x 102, 1.2 x 107. They are ordered from the least to the greatest. eturker|Points 3067|

User: 9. Find the next three terms of the sequence. Then write a rule for the sequence.
648, 216, 72, 24

Weegy: x = y/3
Let x be the unknown
Let y be the known
648
x = y / 3
x = 648 / 3
x = 216
x = y / 3
x = 216 / 3
x = 72
x = y / 3
x = 72 / 3
x = 24
x = y / 3
x = 24 / 3
x = 8
x = y / 3
x = 8 / 3
x = 2.666666667 or 2 and 2/3
x = y / 3
x = ( 2 2/3 ) / [ 3
x = 2.666666667 / 3
x = 0.888888889
x = 8/9
My answers : 648, 216, 72, 24, ___, ___, ___
First term :
8
Second term :
2 and 2/3
Third term :
8 / 9 ( it means 8 over 9 ) ] supernike|Points 610|

User: Solve the equation. Show your work.
163
= 4x

User: _____11. Solve the system using elimination.
3x + 3y = –9
3x – 3y = 21
A. (3, –6)
B. (–5, 2)
C. (3, 3)
D. (2, –5

Weegy: D. (2, 5). The solution for the system of equations 3x + 3y = 9, 3x ? 3y = 21 is (2, -5). Source: eturker|Points 3067|

User: _____13. Simplify the expression.
(k2
)
4
A. k6
B. 2k8
C. k16
D. k

User: _____14. Simplify the expression.
(-8.6)0
A. –1
B. 0
C. –8.6
D. 1

Weegy: (-8.6)^0 = 1

User: 5. Find a pair of factors for each number by using the difference of two squares.
a. 45
b. 77
c. 112

Weegy: So you have an equation of the form
a2?b2
where a=9 and b=2. Thus,
a2?b2=(a?b)?(a+b)
can be replaced by
92?22=(9?2)?(9+2)
Which then simplifies to
7?11 jeifunk|Points 20175|

The next three terms of the sequence 648, 216, 72, 24 is 8, 8/3, 8/9. It is a geometric sequence with common ratio r = 1/3. The rule for this sequence is: a(n) = 648(1/3)^(n-1)

There are no comments.